Two new species of Plutomurus Yosii (Collembola: Tomoceridae) from Georgia and Iran - Barjadze, Shalva; Mayvan, Mahmood Mehrafrooz; Parimuchová, Andrea; Maghradze, Eter; Kováč, Ľubomír (Zootaxa, 2024)
Plutomurus weinerae sp. nov. from Usholta Cave, Racha-Lechkhumi and Kvemo Svaneti region, Georgia, and P. danialensis sp. nov. from Danial Cave, Mazandaran province, Iran are described, illustrated and differentiated from other morphologically similar congeners. New species are distinguishable from similar species by head and abdominal macrochaetotaxy (P. weinerae) and by shorter antennae (P. danialensis). An updated identification key to the species of the genus Plutomurus known from the Western Palearctic is presented. A list of the invertebrate communities for Usholta and Danial caves is provided.